Increase of Production Ratio of Pre-selected Superior Dairy Female Offspring by Combination of OPU derived Oocytes and X-bearing Semen - Seong-Su Kim; Byung-Hyun Choi; Kyeong-Lim Lee; Jong-In Jin; Tae-Kwang Suh; Cheol-Ho Son; Chan-Ho Park; Seung-Oh Shin; Kwang-Jin Han; Hyun-Tae Lim; Kyu-Woan Cho; Il-Keun Kong (The Korean Society of Animal Reproduction and Biotechnology, 2015)
This study was designed to evaluate the possibility of increase through dairy female offspring's ratio by transfer of pre-selected transferrable blastocyst that was produced by pre-selected X-bearing semen with OPU derived oocytes. Elite dairy female cow is demanded strongly compared with male, the so called, farmer wants to produce only an elite female dairy offspring as a candidate female dairy cow for producing milk. In our study, we selected 2 elite dairy bull semen from National Agricultural Cooperative Federation to pre-select X-bearing semen and 5 elite dairy female cows as donor for collecting of OPU derived oocytes. OPU derived embryo production system was carried out an aspiration of immature oocytes from 5 donor cows 2 times per week, total 200 times for 2 to 7 months by an ultrasonographic guided follicular aspiration system and then produced in vitro-produced blastocysts by in vitro maturation, fertilization and culture. Dairy donor semen selected H-319, 320 bull in National Agricultural Cooperative federation was sorted X-bearing semen by flow-cytometer and frozen for using IVF with OPU derived oocytes. Donor cows were selected 5 elite dairy cows from Gyeongju Dairy Cow Community and then disease tests such as 4 kinds of disease before selecting was checked. Oocyte proportion of grade 1 to 3 from total collected oocytes was significantly lower in donor A and B than those in donor C, D and E (82.16 and 70.03% vs. 90.0, 91.78 and 93.57%), respectively (p<0.05). However, number of oocytes per session in donor A, C and E was significantly higher than those in donor B and D (7.77 ± 3.26, 5.85 ± 2.10 and 7.03 ± 2.14 vs. 4.68 ± 2.61 and 5.21 ± 1.97 oocytes), but donor A was significantly higher than donor C (p<0.05). Development to blastocyst in donor B, C and E was significantly higher than those in donor A and D (31.0, 25.0 and 25.0% vs. 14.3 and 4.5%), but donor A was not different in donor C and E (p<0.05). Nine out of 10 blastocysts (90.0%) derived from OPU blastocysts were confirmed male embryos that was induced with Y-bearing semen to confirm sex ratio only. Total 96 blastocysts derived from female bearing semen were transferred into synchronized recipients and then confirmed 42 recipients (43.8%) pregnancy rate, 36 offspring (37.5%) and 91.7% female sex ratio (33 female vs. 3 male offspring). Taken together all data, elite dairy female offspring could be produced effectively by in vitro production system between pre-selected x-bearing semen and OPU derived oocytes that would be influential breeder in the breeding of dairy farm to increase effectively elite dairy offspring ratio as well as net income in the dairy farmer.